Composite catalyst as well as preparation method and application thereof
By preparing a composite catalyst containing components A, B and C catalysts, the problem of difficulty in matching the stability and product distribution of the catalytic cracking device during the start-up stage is solved, and efficient and stable start-up and economic benefits are achieved.
Patent Information
- Application Number
- CN202411463399.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-31
- Filing Date
- 2024-10-21
- Publication Date
- 2025-05-02
AI Technical Summary
There are problems in the existing catalytic cracking devices that are difficult to match stability and product distribution during the start-up stage, especially when using heavier heavy oil, traditional balancer solutions are difficult to efficiently match process conditions, affecting the stable operation and economic benefits of the device.
A composite catalyst is provided, containing components A, B and C catalysts, which are prepared by physical blending. The cracking activity of component A is 55 to 65, component B is a ZSM-5 molecular sieve material, and component C contains modified metal oxides, appropriate particle size distribution and apparent loose density, and is used for the start of a high-density heavy oil catalytic cracking device.
The efficient and stable start of the catalytic cracking device is achieved, and the expected product distribution can be achieved in a short time, reducing the production cost of the catalyst, and improving the economic benefits of the device.
Smart Images

Figure BDA0005092596580000101 
Figure BDA0005092596580000111 
Figure BDA0005092596580000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts and relates to a composite catalyst and a preparation method and application thereof. Background Art
[0002] Catalytic cracking start-up agent is a catalytic cracking catalyst used when a new catalytic cracking unit is built or restarted after a unit is shut down for maintenance. It is generally believed that in order to achieve a smooth start-up of a catalytic cracking unit, the activity of the start-up agent needs to be close to the expected activity value of the balance agent of the target unit, and the distribution of active components and the physical properties of the catalyst particles also need to match the target unit to ensure the stable and safe start-up of the unit, and the product distribution is stable in a short period of time and close to the target product distribution, ensuring economic benefits.
[0003] Traditionally, the start-up agent for new plants generally adopts the balance agent solution, which has many limitations: first, the physical and chemical properties of the balance agents of different plants vary significantly due to the properties of the raw materials, actual operating conditions, etc., and are often difficult to use directly. For example, the use of FCC balance agents in DCC plants will cause key technical indicators such as low-carbon olefins to fail to reach the design values for a long time; second, the market resources for catalytic cracking balance agents are scarce and the quality is uneven; third, different process conditions have different requirements for start-up agents, which are difficult to match efficiently, seriously affecting the stable operation and economic benefits of the plant.
[0004] Technologies for producing light olefins by catalytic cracking of heavier heavy oils, such as the RTC process technology, effectively utilize inferior heavy oils to produce propylene and ethylene, but the existing technology does not have a start-up agent specifically for catalytic cracking of heavier heavy oils. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a composite catalyst used as a start-up agent in the start-up phase of a heavier heavy oil catalytic cracking unit (including shutdown and maintenance start-up, and start-up of a new unit), which can achieve efficient and stable start-up of high-density heavy oil catalytic cracking units such as RTC units.
[0006] Another technical problem to be solved by the present invention is to provide a method for preparing the composite catalyst.
[0007] Another technical problem to be solved by the present invention is to provide a method for starting up a heavier heavy oil, such as an intermediate base heavy oil catalytic cracking unit, such as a method for starting up a RTC process unit.
[0008] In the present invention, the method for measuring the cracking activity refers to the standard NB / SH / T 0952-2017, determination method of micro-reaction activity index of catalytic cracking catalyst. The reaction temperature for measuring the cracking activity of the present invention is 520°C.
[0009] The particle size distribution is measured by laser scattering method, see NB / SH / T 0951-2017, Determination of particle size distribution of catalytic cracking catalysts.
[0010] The apparent bulk density measurement method refers to NB / SH / T 0954-2017, Determination of apparent bulk density of catalytic cracking catalyst.
[0011] The wear index is determined according to the standard NB / SH / T 0964-2017, Determination of wear index of catalytic cracking catalyst, and the straight tube method.
[0012] The coke factor and propylene factor are obtained by "using a fixed fluidized bed evaluation device, the raw oil has a density of 0.91-0.95 kg / m at 20°C 3 The reaction temperature is 570℃, the catalyst-oil ratio is 10 weight ratio, and the weight hourly space velocity is 10h -1 "After the reaction, it is obtained. Coke factor: in the reaction product obtained according to the above method, the yield of coke ÷ the conversion rate; Propylene factor: in the reaction product obtained according to the above method, the yield of propylene ÷ the yield of liquefied gas.
[0013] The first aspect of the present invention provides a composite catalyst, which contains a component A catalyst, a component B catalyst and a component C catalyst. Based on the dry weight of the composite catalyst, the content of the component A catalyst in the composite catalyst is 20 to 90% by weight, the content of the component B catalyst is 5 to 65% by weight, and the content of the component C catalyst is 5 to 15% by weight; wherein,
[0014] The cracking activity of the component A catalyst is 55 to 65;
[0015] The main active component of the component B catalyst is ZSM-5 molecular sieve material;
[0016] The component C catalyst contains a modified metal, wherein the modified metal oxide loading is 2 to 10% by weight, and the modified metal is an alkaline earth metal.
[0017] The second aspect of the present invention provides a method for preparing the composite catalyst, comprising physically mixing component A catalyst, component B catalyst and component C catalyst, wherein:
[0018] The preparation method of the component B catalyst comprises: slurrying a matrix carrier, a ZSM-5 molecular sieve slurry and optionally water, spray drying to obtain first catalyst particles, and optionally calcining;
[0019] The preparation method of the component C catalyst comprises: mixing the matrix carrier with optional water for slurrying, spray drying to obtain second catalyst particles, modifying the modified metal by impregnation, drying, and calcining; or
[0020] The preparation method of the component C catalyst comprises: mixing and slurrying a matrix carrier, a modified metal salt solution and optional water, spray drying to obtain third catalyst particles, and optionally calcining.
[0021] The composite catalyst can be used for the start-up of a heavy oil fluidized catalytic cracking unit, such as a catalytic cracking unit using the RTC process. The RTC process uses a fast bed reactor, whose longitudinal section has an inverted trapezoidal reactor structure, for catalytic cracking of heavy oil.
[0022] In the third aspect of the present invention, the present invention further provides a method for starting up a high-density heavy oil catalytic cracking device, in which the high-density heavy oil is introduced into the catalytic cracking reactor to contact with the fluidized catalyst for catalytic cracking reaction during the start-up phase of the catalytic cracking device, the oil and gas products after the cracking reaction are separated from the catalyst, the catalyst is introduced into the regenerator after gas stripping, regenerated, and then circulated to the catalytic cracking reactor device for reaction, and the oil and gas products are introduced into the subsequent oil and gas separation device for separation, wherein the catalyst is the composite catalyst provided by the present invention. The high-density heavy oil, for example, has a density of 0.91 to 0.95 g / ml at 20°C. In one embodiment, the high-density heavy oil is an intermediate-base heavy oil, and the intermediate-base heavy oil is a heavy oil with a paraffin content of 15 to 25% by weight and a total cycloalkane content of 25 to 35% by weight.
[0023] According to a third aspect of the present invention, in one embodiment, the reactor of the catalytic cracking device is a fast bed reactor, and the longitudinal cross-section of the fast bed reactor has an inverted trapezoidal structure.
[0024] The composite catalyst provided by the present invention has appropriate catalytic cracking activity and product distribution, can simultaneously meet the requirements of fluidization performance on particle size distribution, apparent bulk density and abrasion strength, and can be used as a start-up agent for a heavier heavy oil fluidized catalytic cracking unit to achieve smooth and efficient start-up of the catalytic cracking unit. For example, industrial applications show that when used for the start-up of an RTC unit, the start-up time can be significantly shortened, and the expected product distribution can be achieved within a week.
[0025] The preparation method of the composite catalyst provided by the present invention uses a balance agent and can obtain a catalyst with appropriate activity and product distribution by compounding other appropriate catalyst components. The composite catalyst can have a higher propylene factor and a lower coke factor. Compared with the use of a fresh catalyst, the use of a balance agent can also reduce the preparation cost of the catalyst.
[0026] The high-density heavy oil catalytic cracking device startup method provided by the present invention can realize efficient and stable startup of the device, and can even complete the startup of the device within a week to achieve stable operation. For example, it is used in the startup stage of the RTC process heavy oil catalytic cracking device, such as the startup of a new heavy oil catalytic cracking device or the startup of a heavy oil catalytic cracking device after transformation or overhaul, and can realize efficient and stable startup of the device. DETAILED DESCRIPTION
[0027] According to the present invention, the composite catalyst can be obtained by physically blending component A catalyst, component B catalyst and component C catalyst in a certain proportion. Preferably, in the composite catalyst, on a dry basis, the content of component A catalyst is 75-85% by weight, the content of component B catalyst is 10-20% by weight, and the content of component C catalyst is 5-10% by weight.
[0028] According to the composite catalyst of the present invention, the particle size distribution of the component A catalyst is as follows: the content of particles with a particle size (referring to the diameter, or referred to as particle size) of 0 to 20 μm is ≤3.0v%, the content of particles with a particle size of 0 to 40 μm is ≤18.0v%, the content of particles with a particle size of 0 to 149 μm is ≥90.0v%, and the average particle size is 60.0 to 80.0 μm. Among them, 0 to 20 μm means that the particle size is greater than 0 and does not exceed 20 microns, 0 to 40 μm means that the particle size is greater than 0 and does not exceed 40 microns, and 0 to 149 μm means that the particle size is greater than 0 and does not exceed 149 microns.
[0029] According to the composite catalyst of the present invention, the cracking activity of the component A catalyst is preferably 57-63.
[0030] According to the present invention, in one embodiment, the component A catalyst is a balance agent, which may be a catalytic cracking balance agent, or a treated balance agent obtained by treating the balance agent; the treatment may include demetallization treatment and / or particle size adjustment treatment. The demetallization treatment may adopt one or more of chemical demetallization and physical demetallization treatment. The chemical demetallization treatment may be, for example, an ammonia method or an acid demetallization treatment, the acid method may be, for example, demetallization treatment using a citric acid solution or a sulfuric acid solution, the physical demetallization treatment may be, for example, magnetic separation, the particle size adjustment treatment may be, for example, gas purging to purge out the fine powder therein, or sieving through a sieve. The balance agent is a balance agent produced by a catalytic cracking unit, for example, a balance agent produced by a DCC unit.
[0031] According to the composite catalyst of the present invention, in one embodiment, the specific surface area of the component A catalyst is ≥100m 2 / g; nickel content ≤6000μg / g, vanadium content ≤3000μg / g, rare earth element ≤10000μg / g. For example, the specific surface area of the component A catalyst is 100-200m 2 / g or 100~150m 2 / g; the nickel content is 500-6000μg / g or 200-5800μg / g or 1000-3000μg / g, the vanadium content is 50-3000μg / g or 500-1000μg / g or 300-2800μg / g, and the rare earth element content is 500-10000μg / g or 1000-9500μg / g or 3000-6000μg / g.
[0032] According to the composite catalyst of the present invention, the apparent bulk density of the component B catalyst is 0.80-0.94 g / mL, and the wear index is ≤2.0.
[0033] According to the composite catalyst of the present invention, the content of particles with a particle size of 0 to 20 μm in the component B catalyst is ≤2.0v%, the content of particles with a particle size of 0 to 40 μm is ≤18.0v%, the content of particles with a particle size of 0 to 149 μm is ≥90.0v%, and the average particle size is 60.0 to 85.0 μm.
[0034] According to the composite catalyst of the present invention, the active component of the component B catalyst is a ZSM-5 molecular sieve, and its content is 5 to 15% by weight of the component B catalyst on a dry basis. The ZSM-5 molecular sieve can be, for example, one or more of a hydrogen-type ZSM-5 molecular sieve and a transition metal-modified ZSM-5 molecular sieve, and the transition metal is, for example, one or more of rare earth, iron, cobalt, and nickel. The ZSM-5 molecular sieve can further contain phosphorus. In one embodiment, the ZSM-5 molecular sieve is a multi-level pore ZSM-5 molecular sieve, and the multi-level pore ZSM-5 molecular sieve is, for example, one or more of a hydrogen-type multi-level pore ZSM-5 molecular sieve, or a metal-modified multi-level pore ZSM-5 molecular sieve or a phosphorus-containing metal-modified multi-level pore ZSM-5 molecular sieve. The multi-level pore ZSM-5 molecular sieve can be purchased commercially or prepared according to existing methods. For example, the multi-level pore ZSM-5 molecular sieve can be a hollow multi-level pore ZSM-5 nanocrystalline material, which can be prepared according to the method disclosed in Chinese patent application 202211231700.2 (CN116177561A), for example, the method disclosed in claims 6 to 10 or Examples 1 to 4. ZSM-5 molecular sieves that do not contain mesopores or have a mesopore volume of less than 0.02 ml / g are non-multi-level pore ZSM-5 molecular sieves or conventional ZSM-5 molecular sieves, and those with a mesopore volume greater than 0.2 ml / g are multi-level pore ZSM-5 molecular sieves. The ZSM-5 molecular sieve can be, for example, one or more of a ZRP molecular sieve (a non-multilevel porous phosphorus-containing ZSM-5 molecular sieve), a ZSP molecular sieve (a non-multilevel porous phosphorus-containing and transition metal-containing ZSM-5 molecular sieve), an MPZ molecular sieve (a mesoporous ZSM-5 molecular sieve), and an MPZ molecular sieve containing phosphorus and transition metals (called RMPZ, a mesoporous ZSM-5 molecular sieve).
[0035] According to the composite catalyst of the present invention, the component B catalyst also includes a matrix carrier, and the content of the matrix carrier in the component B catalyst is 85-95% by weight of the component B catalyst on a dry basis, and the matrix carrier is selected from one or more of natural clay, alumina carrier and silica carrier; preferably, the alumina carrier is one or more of aluminum sol, acidified pseudo-boehmite, hydrated alumina and activated alumina; the silica carrier is one or more of neutral silica sol, acidic silica sol or alkaline silica sol.
[0036] In one embodiment, the component B catalyst contains, on a dry basis, 8 to 15 weight percent of active components, 70 to 80 weight percent of kaolin, 3 to 8 weight percent of pseudo-boehmite, 3 to 10 weight percent of aluminum sol, and 2 to 10 weight percent of silica sol.
[0037] According to the composite catalyst of the present invention, the content of the modified metal oxide in the component C catalyst is 2-10%, the content of the carrier is 90-98% by weight, and the metal oxide is an alkaline earth metal oxide. The carrier or matrix carrier is selected from one or more of natural clay, alumina carrier and silica carrier; the alumina carrier is, for example, one or more of aluminum sol, acidified pseudo-boehmite, hydrated alumina and activated alumina; the silica carrier is, for example, one or more of neutral silica sol, acidic silica sol or alkaline silica sol.
[0038] In one embodiment, the component C catalyst contains, on a dry basis, 3 to 8 weight percent of a modified metal oxide, 70 to 85 weight percent of kaolin, 3 to 8 weight percent of pseudo-boehmite, 3 to 8 weight percent of alumina sol, and 2 to 10 weight percent of silica sol.
[0039] According to the composite catalyst of the present invention, the component C catalyst can be obtained by modifying inert microspheres with the modified metal element compound, or by adding the modified metal element compound to an inert microsphere precursor for slurrying and then spray drying.
[0040] According to the composite catalyst of the present invention, in the preparation method of the component C catalyst, the modified metal element compound is one or more of magnesium nitrate, barium nitrate, strontium nitrate or radium nitrate.
[0041] According to the composite catalyst of the present invention, the apparent bulk density of the composite catalyst is 0.90-0.94 g / mL.
[0042] According to the composite catalyst of the present invention, the wear index of the composite catalyst is ≤2.0.
[0043] According to the composite catalyst of the present invention, wherein, in the composite catalyst: nickel content ≤4000 μg / g, vanadium content ≤2500 μg / g, for example, nickel content is 200-4000 μg / g, vanadium content is 300-2500 μg / g.
[0044] According to the composite catalyst of the present invention, wherein, in the composite catalyst: the content of particles with a particle size of 0 to 20 μm is ≤2.0 v%, the content of particles with a particle size of 0 to 40 μm is ≤18.0 v%, the content of particles with a particle size of 0 to 149 μm is ≥90.0 v%, and the average particle size is 65.0 to 85.0 μm.
[0045] According to the composite catalyst of the present invention, the cracking activity of the composite catalyst is preferably 58-62.
[0046] According to the composite catalyst of the present invention, the coke factor of the composite catalyst is ≤0.070, for example, 0.040-0.065.
[0047] According to the composite catalyst of the present invention, the propylene factor of the composite catalyst is ≥ 0.44, for example, 0.44-0.5.
[0048] According to the preparation method of the composite catalyst of the present invention, in the preparation method of the component B catalyst, the matrix carrier is selected from one or more of natural clay, alumina carrier and silica carrier; preferably, the alumina carrier is one or more of aluminum sol, acidified pseudo-boehmite, hydrated alumina and activated alumina; the silica carrier is one or more of neutral silica sol, acidic silica sol or alkaline silica sol.
[0049] In one embodiment, the preparation method of the component B catalyst comprises:
[0050] (1) mixing pseudo-boehmite and water uniformly, adding hydrochloric acid, with an acid-to-aluminum ratio of 0.15 to 0.25 (weight ratio of HCl to pseudo-boehmite calculated as Al2O3), aging at 60 to 75°C for 1 to 2 hours to form a first slurry, wherein the alumina content of the first slurry is preferably 8 to 15 weight %;
[0051] (2) forming a second slurry by combining the first slurry, the active component, aluminum sol, kaolin, optional silica sol and water; the solid content of the second slurry is preferably 20 to 40% by weight;
[0052] (3) spray drying;
[0053] (4) calcination, the calcination temperature is, for example, 500 to 600° C., and the calcination time is, for example, 2 to 5 hours;
[0054] (5) Exchange with ammonium salt.
[0055] In the preparation method of the component C catalyst, the matrix carrier is selected from one or more of natural clay, alumina carrier and silica carrier; preferably, the alumina carrier is one or more of aluminum sol, acidified pseudo-boehmite, hydrated alumina and activated alumina; the silica carrier is one or more of neutral silica sol, acidic silica sol or alkaline silica sol.
[0056] In the preparation method of the component C catalyst, the modified metal is modified by impregnation. The microspheres obtained by spray drying can be mixed with a solution containing a modified metal compound for impregnation, followed by drying and calcination. The impregnation can be, for example, equal volume impregnation or excess impregnation.
[0057] In one embodiment, the preparation method of the component C catalyst comprises:
[0058] A. mixing pseudo-boehmite and water uniformly, adding hydrochloric acid, the acid-aluminum ratio is 0.15-0.25 (the weight ratio of HCl to pseudo-boehmite calculated as Al2O3), aging at 60-75°C for 1-2 hours to form a third slurry, the alumina content of the third slurry is preferably 8-15% by weight;
[0059] B. forming a fourth slurry from the third slurry, aluminum sol, kaolin, optional silica sol and water; the solid content of the fourth slurry is preferably 20 to 40% by weight;
[0060] C. Spray drying;
[0061] D. calcination, the calcination temperature is, for example, 500 to 600° C., and the calcination time is, for example, 1 to 5 hours;
[0062] E. Impregnating the product of step D with an aqueous solution of an alkaline earth metal salt at a temperature of, for example, 40 to 60° C. for a time of, for example, 0.5 to 2.5 hours, drying, and calcining at a temperature of, for example, 500 to 600° C. for a time of, for example, 1 to 5 hours. The impregnation may be equal volume impregnation or excess impregnation.
[0063] In one embodiment, the preparation method of the component C catalyst comprises:
[0064] S1, mixing pseudo-boehmite and water uniformly, adding hydrochloric acid, the acid-aluminum ratio is 0.15-0.25 (the weight ratio of HCl to pseudo-boehmite in terms of Al2O3), aging at 60-75°C for 1-2 hours to form a fifth slurry, the alumina content of the fifth slurry is preferably 8-15% by weight;
[0065] S2, the fifth slurry, alkaline earth metal salt, aluminum sol, kaolin, optional silica sol and water are formed into a sixth slurry; the solid content of the sixth slurry is preferably 20 to 40 weight%;
[0066] S3, spray drying;
[0067] S4, calcining, the calcining temperature is, for example, 500-600° C., and the calcining time is, for example, 1-5 hours.
[0068] In the preparation methods of the component B catalyst and the component C catalyst, the calcination temperature can be 400 to 600° C., and the calcination time can be, for example, 1 to 6 hours.
[0069] According to the preparation method of the composite catalyst described in the present invention, the preparation method of the component B catalyst or the component C catalyst can also further include: mixing the catalyst particles obtained by the spray drying, ammonium salt and water in a weight ratio of 1: (0.1-1): (5-15) to perform ammonium exchange, and optional washing, so that the Na2O content in the catalyst microspheres is less than 0.15 weight%; the catalyst particles obtained by spray drying are the first catalyst particles, the second catalyst particles or the third catalyst particles.
[0070] In one embodiment, the conditions for the ammonium exchange include: a temperature of 50-100° C. and a time of 0.5-2 hours. The ammonium salt may be selected from one or more of ammonium chloride, ammonium sulfate and ammonium nitrate.
[0071] The following examples are used to describe the specific embodiments of the present invention in detail. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0072] The balance agents P1 and P2 used in the comparative example are balance agents produced by a catalytic cracking unit, and their properties are shown in Table 1.
[0073] Component A catalyst A1 is a treated balance agent obtained by subjecting the catalytic cracking balance agent of the catalytic cracking process to cyclotron fractionation and acid demetallization treatment, and its properties are shown in Table 1.
[0074] Component A catalyst A2 is a treated balance agent obtained by subjecting the catalytic cracking balance agent of the catalytic cracking process to cyclotron fractionation and acid demetallization treatment, and its properties are shown in Table 1.
[0075] Raw materials used: aluminum sol (product of Sinopec Catalyst Qilu Branch, with an Al2O3 content of 21.5% by weight); silica sol (product of Qingdao Junqiang New Materials Co., Ltd., with an SiO2 content of 30% by weight and a pH value of 9.5); kaolin (product of Suzhou China Kaolin Company, with a solid content of 76% by weight). Pseudo-boehmite, a product of Shandong Aluminum Company, with an Al2O3 content of 62% by weight.
[0076] Example 1
[0077] (1) The balance agent 1 from the catalytic cracking unit is subjected to physical cyclone treatment (fine components are separated by a cyclone separator) to reach a certain particle size requirement; and then subjected to chemical demetallization treatment (the catalytic cracking balance agent is contacted with a sulfuric acid solution to react with harmful metals such as vanadium, nickel, iron, and sodium deposited on the balance agent, thereby partially removing these harmful metals and reducing their toxicity.) to reach a certain metal content, thereby obtaining component A catalyst 1, denoted as A1, with physical property parameters shown in Table 1.
[0078] (2) Component B catalyst:
[0079] Mix pseudo-boehmite and water evenly, add concentrated hydrochloric acid with a concentration of 36 weight % under stirring, and the acid-aluminum molar ratio is 0.2 (the molar ratio of HCl to pseudo-boehmite calculated as Al2O3); age the resulting mixture at 70°C for 1.5 hours to obtain an aged pseudo-boehmite slurry. The aged pseudo-boehmite slurry has an alumina content of 12 wt%; ZRP-1 molecular sieve (a product of Sinopec Catalyst Qilu Branch, with a silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of 25 and a phosphorus (P2O5) content of 3.5 wt%), aluminum sol, silica sol, kaolin, the aged pseudo-boehmite slurry and deionized water are uniformly mixed to form a slurry with a solid content of 30 wt%, and spray-dried to obtain component B catalyst microspheres; the component B catalyst microspheres are calcined at 550°C for 4h; the calcined component B catalyst microspheres are exchanged at 80°C for 1h according to a weight ratio of component B catalyst microspheres: ammonium salt: H2O=1:1:10, filtered, the above exchange and filtration process is repeated once, and dried, wherein the ammonium salt is ammonium chloride, and the sodium oxide content in the obtained component B catalyst is less than 0.15 wt%, recorded as B1.
[0080] (3) Component C catalyst:
[0081] Pseudo-boehmite and water are uniformly mixed, and concentrated hydrochloric acid with a concentration of 36% by weight is added under stirring, and the acid-aluminum molar ratio is 0.2 (the molar ratio of HCl to pseudo-boehmite calculated as Al2O3); the resulting mixture is aged at 70°C for 1.5 hours to obtain an aged pseudo-boehmite slurry. The aged pseudo-boehmite slurry has an alumina content of 12% by weight; aluminum sol, silica sol, kaolin, the aged pseudo-boehmite slurry and deionized water are uniformly mixed to form a slurry with a solid content of 30% by weight, spray dried, and calcined at 550°C for 4 hours; spray-dried microspheres 1 are obtained;
[0082] Prepare a magnesium nitrate solution by dissolving 18.4 g of magnesium nitrate in 50 g of deionized water. Use the prepared magnesium nitrate solution to impregnate the spray-dried microspheres 1 at a temperature of 50° C. for 2 hours, and directly dry and calcine to obtain a component C catalyst, which is recorded as C1.
[0083] (4) The catalyst component A, the catalyst component B and the catalyst component C are mixed uniformly in a certain ratio (see Table 1 for the ratio), which is the composite catalyst of Example 1.
[0084] Example 2
[0085] (1) Component A catalyst is a balance agent from a catalytic cracking unit. It is physically cyclonized to reach a certain particle size requirement. It is then chemically demetallized by sulfuric acid solution to reach a certain metal content. The physical properties are shown in Table 1 and are denoted as A2.
[0086] (2) Component B catalyst:
[0087] Pseudo-boehmite and water were mixed evenly, and concentrated hydrochloric acid with a concentration of 36% by weight was added under stirring, and the acid-aluminum ratio was 0.2 (the weight ratio of HCl to pseudo-boehmite in terms of Al2O3); the resulting mixture was aged at 70°C for 1.5 hours to obtain an aged pseudo-boehmite slurry. The aged pseudo-boehmite slurry had an alumina content of 12% by weight; RMPZ molecular sieve (a product of Sinopec Catalyst Co., Ltd. Qilu Branch, with a phosphorus content (in terms of P2O5) of 3.4% by weight, a Fe2O3 content of 2.3% by weight, a silicon-aluminum ratio of 25, and a mesopore volume of 0.12 cm 3 / g;), aluminum sol, silica sol, kaolin and the above-mentioned aged pseudo-boehmite slurry and deionized water are uniformly mixed to form a slurry with a solid content of 30% by weight, and spray-dried to obtain component B catalyst microspheres; the component B catalyst microspheres are calcined at 550°C for 4h; the calcined component B catalyst microspheres are exchanged at 80°C for 1h according to a weight ratio of component B catalyst microspheres: ammonium salt: H2O = 1:1:10, filtered, the above-mentioned exchange and filtration process is repeated once, and dried, wherein the ammonium salt is ammonium chloride, and the sodium oxide content in the obtained component B catalyst is less than 0.15% by weight, recorded as B2.
[0088] (3) Component C catalyst:
[0089] Pseudo-boehmite and water are mixed uniformly, and concentrated hydrochloric acid with a concentration of 36% by weight is added under stirring, and the acid-aluminum molar ratio is 0.2 (the molar ratio of HCl to pseudo-boehmite calculated as Al2O3); the resulting mixture is aged at 70°C for 1.5 hours to obtain an aged pseudo-boehmite slurry. The aged pseudo-boehmite slurry has an alumina content of 12% by weight; barium nitrate solution (10.2 grams of barium nitrate is dissolved in 50 grams of deionized water), aluminum sol, silica sol, kaolin and the above-mentioned aged pseudo-boehmite slurry and deionized water are uniformly mixed to form a slurry with a solid content of 30% by weight, spray dried, and calcined at 550°C for 4 hours to obtain a component C catalyst, recorded as C2.
[0090] (4) The component A catalyst A2, the component B catalyst B2 and the component C catalyst C2 are mixed evenly in a certain ratio (85:10:5 by weight) to obtain the composite catalyst of Example 2.
[0091] Comparative Example 1
[0092] The catalyst in Comparative Example 1 is conventional balancing agent P1, and the physical property parameters of P1 are shown in Table 1.
[0093] Comparative Example 2
[0094] The catalyst in Comparative Example 2 is conventional balancing agent P2, and the physical properties of P2 are shown in Table 1.
[0095] Table 1 Parameters of Examples and Comparative Examples
[0096]
[0097]
[0098] Performance Testing
[0099] The composite catalyst prepared in the embodiment and the comparative example was used to evaluate its cracking reaction performance in a FFB fixed fluidized bed reactor. The evaluation conditions were: reaction temperature 570°C, catalyst-oil ratio 10 weight ratio, and weight hourly space velocity 10h -1 The raw material is heavy oil. The physical properties are shown in Table 2. The evaluation results are shown in Table 3.
[0100] Table 2 Heavy oil properties
[0101]
[0102] Table 3 Catalytic performance evaluation results
[0103] Catalyst source Example 1 Example 2 Comparative Example 1 Comparative Example 2 Lysis activity 59.0 59.4 79.6 80.9 Reaction performance Coke Factor 0.045 0.043 0.085 0.083 Propylene Factor 0.468 0.470 0.350 0.351
[0104] The yields mentioned herein are calculated based on the raw material feed.
[0105] Product yield = product yield (weight) / heavy oil feed amount (weight)
[0106] Coke factor = coke yield (weight) / conversion rate
[0107] Propylene factor = Propylene yield (weight) / Liquefied gas yield
[0108] It can be seen from Table 3 that the composite catalyst provided by the present invention has a significantly higher propylene factor and a significantly lower coke factor.
Claims
1. A composite catalyst comprising: (1) 20 to 90% by weight of a catalyst of component A, wherein the cracking activity of the catalyst of component A is 55 to 65, (2) 5 to 65 wt% of component B catalyst, wherein the main active component of the component B catalyst is ZSM-5 molecular sieve, (3) 5 to 15 wt% of component C catalyst, wherein the component C catalyst contains 2 to 10 wt% of a modified metal oxide, wherein the modified metal is an alkaline earth metal.
2. The composite catalyst according to claim 1, wherein The component A catalyst is a balance agent and / or a treated balance agent obtained by treating the balance agent; the treatment may include a demetallization treatment and / or a particle size adjustment treatment; The specific surface area of the component A catalyst is ≥100m 2 / g; nickel content ≤6000μg / g, vanadium content ≤3000μg / g, rare earth element ≤10000μg / g; for example, the specific surface area of the component A catalyst is 100-200m 2 / g; the nickel content is 500-6000 μg / g, the vanadium content is 50-3000 μg / g, and the rare earth element content is 500-10000 μg / g; the cracking activity of the component A catalyst is preferably 57-63; Optionally, the particle size distribution of the component A catalyst is: the content of particles with a particle size of 0 to 20 μm is ≤3.0 v%, the content of particles with a particle size of 0 to 40 μm is ≤18.0 v%, the content of particles with a particle size of 0 to 149 μm is ≥90.0 v%, and the average particle size is 60.0 to 80.0 μm.
3. The composite catalyst according to claim 1, wherein The component B catalyst has an apparent bulk density of 0.80 to 0.94 g / mL and an abrasion index of ≤2.0; Preferably, in the component B catalyst, the content of particles with a particle size of 0 to 20 μm is ≤2.0 v%, the content of particles with a particle size of 0 to 40 μm is ≤18.0 v%, the content of particles with a particle size of 0 to 149 μm is ≥90.0 v%, and the average particle size is 60.0 to 85.0 μm; Preferably, the component B catalyst comprises: 5 to 15 weight percent ZSM-5 molecular sieve on a dry basis, and 85 to 95 weight percent matrix carrier on a dry basis; The matrix carrier is selected from one or more of natural clay, alumina carrier and silica carrier; preferably, the alumina carrier is one or more of aluminum sol, acidified pseudo-boehmite, hydrated alumina and activated alumina; the silica carrier is one or more of neutral silica sol, acidic silica sol or alkaline silica sol.
4. The composite catalyst according to claim 1, wherein The component C catalyst contains 2-10 wt% of modified metal oxide and 90-98 wt% of carrier; the metal oxide is an alkaline earth metal oxide; the carrier is selected from one or more of natural clay, alumina carrier and silica carrier; the alumina carrier is, for example, one or more of aluminum sol, acidified pseudo-boehmite, hydrated alumina and activated alumina; the silica carrier is, for example, one or more of neutral silica sol, acidic silica sol or alkaline silica sol; The component C catalyst can be obtained by modifying inert microspheres with the modified metal element compound, or by adding the modified metal element compound to an inert microsphere precursor for slurrying and then spray drying; the modified metal element compound is, for example, one or more of magnesium nitrate, barium nitrate, strontium nitrate or radium nitrate.
5. The composite catalyst according to claim 1, wherein The composite catalyst has an apparent bulk density of 0.90 to 0.94 g / mL, and an abrasion index of ≤2.0; in the composite catalyst, the content of particles with a particle size of 0 to 20 μm is ≤2.0 v%, the content of particles with a particle size of 0 to 40 μm is ≤18.0 v%, the content of particles with a particle size of 0 to 149 μm is ≥90.0 v%, and the average particle size is 65.0 to 85.0 μm; Preferably, in the composite catalyst: the nickel content is ≤4000 μg / g, and the vanadium content is ≤2500 μg / g, for example, the nickel content is 200-4000 μg / g, and the vanadium content is 300-2500 μg / g.
6. The composite catalyst according to claim 1, wherein The cracking activity of the composite catalyst is 58-62, the coke factor of the composite catalyst is ≤0.070, such as 0.040-0.065, and the propylene factor of the composite catalyst is ≥0.44, such as 0.44-0.
5.
7. The composite catalyst according to claim 1, wherein The content of the catalyst of component A is 75-85% by weight, the content of the catalyst of component B is 10-20% by weight, and the content of the catalyst of component C is 5-10% by weight.
8. A method for preparing the composite catalyst according to claim 1, comprising physically mixing component A catalyst, component B catalyst and component C catalyst, wherein the preparation method of component B catalyst comprises: Slurrying a slurry of a matrix support, a ZSM-5 molecular sieve and optionally water, spray drying to obtain first catalyst particles, and optionally calcining; The preparation method of the component C catalyst comprises: mixing the matrix carrier with optional water for slurrying, spray drying to obtain second catalyst particles, modifying the modified metal by impregnation, drying, and calcining; or The preparation method of the component C catalyst comprises: mixing and slurrying a matrix carrier, a modified metal salt solution and optional water, spray drying to obtain third catalyst particles, and optionally calcining. The matrix carrier is selected from one or more of natural clay, alumina carrier and silica carrier; The preparation method of the component B catalyst or the component C catalyst may also further include: mixing the catalyst particles obtained by spray drying, ammonium salt and water to perform ammonium exchange, and optionally washing to make the Na2O content in the catalyst microspheres less than 0.15 weight %; the catalyst particles obtained by spray drying are the first catalyst particles, the second catalyst particles or the third catalyst particles.
9. A method for starting up a high-density heavy oil catalytic cracking device, wherein during the start-up phase of the catalytic cracking device, heavier heavy oil is introduced into a catalytic cracking reactor to contact with a fluidized catalyst for catalytic cracking reaction, the oil and gas products after the cracking reaction are separated from the catalyst, the catalyst is introduced into a regenerator for regeneration after gas stripping, and then circulated to the catalytic cracking reactor device for reaction, and the oil and gas products are introduced into a subsequent oil and gas separation device for separation, wherein the catalyst is the composite catalyst according to any one of claims 1 to 7; In one embodiment, the longitudinal cross-section of the reactor of the catalytic cracking device has an inverted trapezoidal structure.
10. Use of the composite catalyst according to any one of claims 1 to 7 in the start-up of a device using the RTC process.
Citation Information
Patent Citations
ZSM-5 nanocrystalline material with hollow hierarchical pores as well as preparation method and application of ZSM-5 nanocrystalline material
CN116177561A